The morphology of Anoplostoma cuticularia n. sp. (Nematoda, Enoplida) and the position of Anoplostomatidae Gerlach et Riemann, 1974 in the system of nematoda (Translated from Russian) - Belogurov, O. I.; Alekseev, V. M. (Zool. Zh., 1977)
Locality: ; Cabinet:n980
NeMys doc_id: 6102